(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Many face organs are exposed to different environmental conditions in terms of different ofambient temperature, degradation, discoloration, changes in humidity and especiallyfrequent washing of these organs. These conditions cause changes in the structure ofmaterials so, for restoring the function and improving aesthetics of the affected areas ofmaxillofacial by surgical reconstruction and prosthetic rehabilitation the silicone rubbers(SR) and PMMA are the materials of choice. So that, the aim of this research is toinvestigate the effect of addition of polymethyl methacrylate (PMMA) material on thephysical properties of blends from SR/PMMA at different weight percentage (5%, 10%,15% and 20%) of PMMA to silicone rubber. Fourier transform infrared spectrometer test )FTIR(, density, water absorption and thermal properties were done on the all preparedsamples, which are used for maxillofacial prostheses applications. The results showed thatthere is good correlation in FTIR spectrum for reference silicone rubber and (SR/PMMA)polymer blend and this confer a good compatibility between silicone rubber matrix materialand PMMA. As well as the physical properties showed that the favorite percent of PMMA is10% which has ideal characteristic. So, this sample may be a suitable material to achieve theproperties required for maxillofacial prosthetic applications.